Adenovirus-mediated gene transfer of a secreted form of human macrophage scavenger receptor inhibits modified low-density lipoprotein degradation and foam-cell formation in macrophages. - Laukkanen, J; Lehtolainen, P; Gough, P; Greaves, D; Gordon, S; Ylä-Herttuala, S (2000)
BACKGROUND: Macrophage scavenger receptors (MSRs) play an important role in the pathogenesis of atherosclerosis. Therefore, local modulation of MSR activity could have a beneficial effect on atherogenesis. METHODS AND RESULTS: We cloned a secreted "decoy" MSR (sMSR) that contains an extracellular portion of the human MSR type AI and constructed an adenoviral vector that directs high-level expression of sMSR in macrophages under the control of the human CD68 promoter. Expression of the sMSR protein inhibited the degradation of (125)I-labeled acetylated LDL and oxidized LDL by murine macrophages up to 90%. sMSRs also reduced acetylated LDL degradation in MSR knockout mouse peritoneal macrophages by 60% to 80%, which suggests that the decoy construct can compete for the uptake mediated via other related scavenger receptors. In addition, sMSRs inhibited foam-cell formation in murine macrophages in the presence of cytochalasin D. The mechanism of inhibition is through ligand binding to the sMSRs, which prevents the ligand binding to MSRs on cell membranes. CONCLUSIONS: The demonstration that recombinant adenovirus-mediated gene transfer of decoy sMSRs can block foam-cell formation suggests a possible new strategy for gene therapy of atherosclerosis and for the treatment of lipid accumulation after arterial manipulations.